Kontekstualisasi Tafsir Feminis Amina Wadud pada Masyarakat Islam di Indonesia - Rini Rini (Institut Agama Islam Negeri (IAIN) Curup, 2019)
Amina Wadud is one of the feminist figures, who tries to give a new color in the interpretation of the contemporary Qur'an. Amina Wadud as a woman tries to accommodate the voice of women in every interpretation of the verses of the Qur'an. This article aims to conduct an analytical study of the contextualization of feminist interpretations conducted by Amina Wadud which includes the methodology of interpretation carried out and several examples of Amina Wadud's interpretations and the author's analysis of the contextualization of Amina Wadud's interpretation of Islamic society. The method used in this study is the library research method. The result of this study is that in making his interpretation, Amina Wadud uses an interpretation model called hermeneutics. The method of hermeneutical interpretation is intended to obtain conclusions on the meaning of a text or verse. The contextualization of feminine interpretations of Amina Wadud in Islamic society in Indonesia, especially feminist activists, among others, is the equal rights and obligations between husband and wife in family life.